The public in Aotearoa New Zealand support policies to reduce alcohol harm: results from a national survey - Rose Crossin; Ella Iosua; Emma Shields; Andrew Gray; Louise Signal; Rana Peniamina; Bronwen McNoe (New Zealand Medical Journal, 2026)
aim: Alcohol consumption is a cause of at least seven types of cancer and contributes substantially to Aotearoa New Zealand’s cancer burden; population-level interventions are one way to reduce this burden. This study therefore investigates: 1) public support for increased action by politicians to reduce alcohol-related harm, and 2) what policies are both strongly supported by the public and have high consistency of support by voting intention. methods: Data are from a nationally representative, cross-sectional online survey examining public support for evidence-based cancer-related policies in Aotearoa New Zealand. results: We used oversampling to include a sufficient number of Māori (n=385, 23.5% of the sample) and Pacific people (n=368, 22.5%) among our sample of n=1,635. An estimated 71.1% of the population think politicians should do more to keep people safe from alcohol harm, with majority support across the political spectrum. There was overall majority support for each of the 10 alcohol policies/laws proposed, and cross-party support by voting intention across six policies. Support ranged from 54.9% for increasing the price of alcohol using excise tax to 84.4% for improved online alcohol delivery safeguards. conclusion: There is strong public support for politicians and the government to act, and to introduce evidence-based alcohol policies recommended by the World Health Organization, with the aim of reducing alcohol-related health burdens, including cancer.